2011
DOI: 10.1007/s12288-011-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia Care in India: A Review and Experience from a Tertiary Care Centre in Uttar Pradesh

Abstract: Approximately 14,000 people with hemophilia are registered at the Hemophilia Federation of India; however, hemophilia remains under-diagnosed and many cases are not registered. In June 2009, the Government of Uttar Pradesh made anti-hemophilic factors available at a few centers, including the Sanjay Gandhi Post Graduate Institute of Medical Sciences, Lucknow. Consequently, the level of hemophilia care has improved considerably in recent times. Amongst the many challenges facing people with hemophilia, the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…6 Another study conducted in western world also resulted in same findings but these findings differ from a study conducted in India which states that it is expected that patients will develop inhibitors within 10-15 exposure days. 7,8 In our study we observed that 80% patients who develop inhibitor had 1 st exposure in their infancy. This finding is similar to other study done in other part of world.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…6 Another study conducted in western world also resulted in same findings but these findings differ from a study conducted in India which states that it is expected that patients will develop inhibitors within 10-15 exposure days. 7,8 In our study we observed that 80% patients who develop inhibitor had 1 st exposure in their infancy. This finding is similar to other study done in other part of world.…”
Section: Discussionmentioning
confidence: 47%
“…Findings from Indian studies show prevalence of inhibitors ranging from 5.1% to 13% in different studies. 6,8,10 Studies from other parts of world shows a higher prevalence ranging from 24-30%. 6,9,11,12 Keeping these facts in mind it is necessary to identify patients with inhibitors and provide treatment facilities to them so these patients can lead a productive life because management of Hemophilia patients with inhibitor is very difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary prophylactic treatment with recombinant FVIII is the preferred treatment modality in patients with severe haemophilia A due to its improved outcome over secondary prophylaxis (prophylaxis started after the onset of clinically relevant joint damage) and on‐demand therapy . However, in many developing countries, primary prophylaxis is not implementable due to the lack of available FVIII . Despite having a large number of the world's haemophilia patients, developing countries have access to relatively small amounts of the expensive (~US$ 1.1 per unit) clotting factors and must therefore ‘do more with less’ .…”
Section: Introductionmentioning
confidence: 99%
“…However, the current case detection in India is much lower than the USA, which has an excellent Haemophilia surveillance system in comparison . WFH data suggest that only 20% of people with a bleeding disorder in India are diagnosed . Thus, underdiagnoses of bleeding disorders in developing countries such as India are evident.…”
Section: Introductionmentioning
confidence: 99%